2021
DOI: 10.1037/adb0000677
|View full text |Cite
|
Sign up to set email alerts
|

Indigenously adapted cognitive–behavioral therapy for excessive smartphone use (IACBT-ESU): A randomized controlled trial.

Abstract: This study aims to assess whether 12 sessions of indigenously adapted cognitive-behavioral therapy for excessive smartphone use (IACBT-ESU) would reduce excessive smartphone use. A single-blind randomized controlled trial was conducted in students (12 to 19 years of age) to examine the potential beneficial effects of IACBT-ESU (n ϭ 62) compared with brief educational data alone (n ϭ 62). Symptoms of depression, anxiety, stress, and peer relations were also compared between the two groups. The IACBT-ESU group d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…In a recent RCT, Turel [30] found that a brief period of abstinence from social media is only effective in restoring (perceived) agency over social media use among users with high cognitive reflection tendencies, suggesting that the very susceptibilities that may lead social media overuse limit the success of detox interventions. An alternative are treatments that focus on retraining the brain in an attempt to remedy executive functioning deficits, for example, by strengthening individuals through cognitive behavioral therapy (e.g., [31,32,33]). However, such treatment methods are also in doubt as a recent meta-analysis finds them largely ineffective [34].…”
Section: Social Media As a Drugmentioning
confidence: 99%
“…In a recent RCT, Turel [30] found that a brief period of abstinence from social media is only effective in restoring (perceived) agency over social media use among users with high cognitive reflection tendencies, suggesting that the very susceptibilities that may lead social media overuse limit the success of detox interventions. An alternative are treatments that focus on retraining the brain in an attempt to remedy executive functioning deficits, for example, by strengthening individuals through cognitive behavioral therapy (e.g., [31,32,33]). However, such treatment methods are also in doubt as a recent meta-analysis finds them largely ineffective [34].…”
Section: Social Media As a Drugmentioning
confidence: 99%